Musculoskeletal Disorders Complaints in Dentists: A Systematic Literature Review - Dwi Windu Kinanti Arti; Yuliani Setyaningsih; Mohammad Zen Rahfiludin; Henry Setyawan Susanto (Indonesian Journal of Global Health Research, 2025)
The profession of dentistry is a job that is at risk of musculoskeletal disorders. Dentists often work in static and non-ergonomic positions for long periods of time, perform repetitive movements, and interact with patients in limited workspaces. A comprehensive understanding of the prevalence, location of complaints, and the most dominant risk factors is needed to develop effective prevention and intervention strategies to reduce musculoskeletal disorders. Objective to identify musculoskeletal disorders in dentists along with prevalence, pain areas and risk factors. The author used the PRISMA checklist to guide the selection of articles. The databases used were Science Direct and Scopus to search for academic articles published between 2020 and 2025 that met the predetermined content criteria with the keywords Musculoskeletal Disorders, Dentist, Dental, Prevalence, Work Related and Risk Factors. Initial findings based on keywords obtained 494 articles, then screening was carried out until 10 relevant articles to review. The prevalence of MSDs complaints reported in each article was between 58.3% - 93%. The highest pain areas in dentists were in the neck, lower back and shoulders. One of the most dominant risk factors is work posture. Musculoskeletal Disorders (MSDs) are occupational health problems that are often experienced by dentists. Risk factors for MSDs are divided into individual characteristics, jobs, habits, and work environments. Interventions are needed to prevent MSDs in dentists such as ergonomic interventions and education since professional education.